History of Geography as a Science in the Republic of Paraguay. - Yacher, Leon I. (2010)
Keywords: dept.egm; faculty_collection; sabbatical_report

Raptors of the Northeast - Bosakowski, Thomas; Smith, Dwight G. (Coachwhip Publications, 2010)
Keywords: Birds of prey; Identification; Identification; Birds; Northeastern States; dept.egm; faculty_collection

Sabbatical leave report: sabbatical Spring 2010 - Yacher, Leon I. (2010)
The purpose of the project was to travel to Paraguay to explore the history of geography as a science in that country, including identifying the foremost geographers who helped introduce and establish geography as a science in that country. No such study on the history of geography in Paraguay had been previously undertaken anywhere. Further research will be needed, but the collected material is ample for at least two article-length publications.
Keywords: dept.egm; faculty_collection

Mobility, farmworkers, and Connecticut's tobacco valley, 1900–1950 - Harrison, Blake (Journal of Historical Geography, 2010)
By the early decades of the twentieth century, southern New England's Connecticut Valley had become a center of shade tobacco production and a destination for seasonal farmworkers drawn from sources inside and outside of New England. This paper explores the history of three groups of seasonal workers-children from area cities and towns; white southern high school students: and young African American men from southern high schools and black colleges-with an eye to assessing the impact of their presence on the form and meaning of the Connecticut Valley. My first goal is to add depth to the historiography of twentieth-century New England farming by drawing attention to the largely overlooked story of non-rural and extra-regional seasonal farmworkers. My second goal is to frame the case of Connecticut tobacco labor according to the study of mobility and its relationship to landscape. The mobility of workers into and within the region, I suggest, made possible the success of the shade tobacco economy while at the same time posing challenges to popularized cultural conventions about regional identity. For this reason, I argue, the history of Connecticut's shade tobacco landscape was informed by the efforts of shade tobacco growers to direct and control a confluence of environmental conditions, group and place-based identities, and the mechanics and meanings of mobility among seasonal workers. By hiring non-local, seasonal workers and by attempting to control their mobility, large-scale, corporate growers and their spokespeople ultimately sought to maintain control over the development and identity of the valley's rural landscape. (C) 2009 Elsevier Ltd. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/074-295-443-843-273 tex.type: [object Object]
Keywords: Agriculture; Connecticut; Connecticut Valley; Labor; Mobility; New England; Nicotiana tabacum; Tobacco; United States; agricultural production; dept.egm; environmental conditions; mobility; rural landscape; tobacco; twentieth century

Jaltomata parviflora (Solanaceae) una nueva especie del Norte del Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2010)
Citation Key Alias: pop00185 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

Book Review: A review of “Cultural landscapes” - Yacher, Leon (The Professional Geographer, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/150-201-209-871-369 tex.type: [object Object]
Keywords: book.review; dept.egm

Photojournal: distant beats: tradition and change in senegal - Yacher, Leon (Focus on Geography, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-871-272-049-905 tex.type: [object Object]
Keywords: Senegal; cultural change; cultural geography; cultural influence; cultural landscape; cultural tradition; dept.egm; music